Study of current prescribing pattern of antimicrobial drugs in indoor cases of enteric fever in a tertiary care hospital - Rathod, Pravin S.; Patil, Praveenkumar T.; Choure, Balwant K.; Patil, A. W. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Rational antibiotic prescription is very important to prevent antimicrobial resistance. Hence the present study was conducted to evaluate the prescribing pattern of antimicrobial drugs in indoor enteric fever patients of medicine and paediatric department of a tertiary care hospital. Methods: A retrospective study of 2 months duration was undertaken during July and August of 2015. A total number of 97 enteric fever patients’ case sheets were utilized for our study from medicine and paediatric in-patients department of a tertiary care hospital. The data was analysed and results were expressed as percentage. Results: Out of 97 enteric fever patients, 54.64% were females. 13.4% of paediatric population were suffered because of enteric fever. The incidence of enteric fever was 74.23% in 13-40 years. Most commonly prescribed antimicrobials were 3rd generation cephalosporins and fluoroquinolones. 43.30% patients received more than one antibiotic. Antimalarials chloroquine, artemisinin derivatives and metronidazole were other drugs prescribed to enteric fever patients concurrently for associated clinical conditions. Conclusions: Interventional programme should focus on the use of rational antibiotic prescription aimed at minimizing unnecessary cost, adverse drug reactions and emergence of bacterial resistance.